Pengembangan bahan ajar modul berbasis discovery learning pada materi laju reaksi - Silaban, Leady Tresia; Sinaga, Marudut (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to analyze the effect of developing discovery-learning-based module teaching materials on reaction rate material. This type of research is called research and development (R&D). The sampling technique used was random sampling. The sample used is one class, namely class XI MIA 2, as an experimental class. The research instruments used in this study were both test instruments and non-test instruments. After obtaining the research data, the prerequisite tests were carried out, namely the normality test and the homogeneity test, finally making a decision. The discovery-based chemistry learning module on reaction rate material has been proven to be in accordance with BSNP. This module has also been effective in improving student learning outcomes, indicating a significant increase in understanding. In addition, at the limited dissemination stage, this module received very high ratings in various aspects, indicating great benefits for students in understanding chemistry materials on reaction rates. Thus, it can be concluded that there is an effect of developing discovery-learning-based module teaching materials on reaction rate material.